RUU 355 rallies: Gauging support for Islamic law in Malaysia - Rashaad Ali (2017)
The proposed changes to Malaysia’s Criminal Jurisdiction Act 1965 – also known as Act 355 – seek to raise the penalties for certain crimes under Shariah jurisdiction. The move has provoked strong public reaction, as seen in two rallies on 18 February 2017. The controversy demonstrates a nation still divided over race and religion amid a looming general election.